Hubungan Umur Paritas dan Anemia dengan Kejadian Perdarahan Postpartum di Rumah Sakit Bhayangkara Palembang Tahun 2021 - Meli Rosita; Andini Zuitasari; Rizki Amalia (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
Post-partum by WHO as a state of blood loss > 500 ml in 24 hours after delivery. Age is a factor in the occurrence of postpartum hemorrhage. Women who give birth to children at the age of more than 35 years is a predisposing factor for postpartum hemorrhage which can lead to maternal death. This study aims to determine the relationship between age, parity and anemia with the incidence of postpartum hemorrhage at Bhayangkara Hospital Palembang. This study used an analytical survey with a Cross Sectional design. as many as 73 (100%) samples obtained there are 4 patients who have an age with a risk of 5% while patients whose age is not dangerous are 69 patients or 95%. from a total of 73 (100%) samples. There were more patients with high parity than those with low parity. There were 42 patients or 58% who had high parity while there were 31 patients who had low parity, namely 42%. From the total sample of 73 patients, there were 15% or 11 who suffered from anemia while those who did not suffer from anemia were 62 patients with a percentage of 85%. There was a significant relationship between age and the incidence of bleeding at Bhayangkara Hospital Palembang in 2021. From the results of statistical tests with a p value = 0.003 or p < 0.05. There is no significant relationship between parity and the incidence of bleeding at Bhayangkara Hospital Palembang in 2021. This is based on the results of statistical tests with p value = 0.716 or p> 0.05. There is a significant relationship between anemia with bleeding events at Bhayangkara Hospital. This is based on the results of statistical tests with p value = 0.000 or p < 0.05.Â